2020
DOI: 10.1186/s13550-020-00733-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of digital and conventional PET control databases for semi-quantitative analysis of brain 18F-FDG digital PET scans

Abstract: Purpose Digital PET cameras markedly improve sensitivity and spatial resolution of brain 18F-FDG PET images compared to conventional cameras. Our study aimed to assess whether specific control databases are required to improve the diagnostic performance of these recent advances. Methods We retrospectively selected two groups of subjects, twenty-seven Alzheimer's Disease (AD) patients and twenty-two healthy control (HC) subjects. All subjects underwent a brain 18F-FDG PET on a digital camera (Vereos, Philips®… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
0
6
0
3
Order By: Relevance
“…New metrics that may be more suited for advanced reconstructions, e.g., based on SUVpeak for lesional uptake [ 56 , 72 ], should also be explored in such clinical trial datasets. Besides Deauville scores and other established diagnostic cut-offs [ 65 ], such studies may address the influence on prognostic cut-offs [ 58 ] or on normal databases [ 91 , 92 ]. Using either approach, non-inferiority of the new standard regarding clinical endpoints must be well proven, before it can be used safely to guide crucial clinical decisions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…New metrics that may be more suited for advanced reconstructions, e.g., based on SUVpeak for lesional uptake [ 56 , 72 ], should also be explored in such clinical trial datasets. Besides Deauville scores and other established diagnostic cut-offs [ 65 ], such studies may address the influence on prognostic cut-offs [ 58 ] or on normal databases [ 91 , 92 ]. Using either approach, non-inferiority of the new standard regarding clinical endpoints must be well proven, before it can be used safely to guide crucial clinical decisions.…”
Section: Discussionmentioning
confidence: 99%
“…• Image noise [75][76][77][78] • Subjective image quality [73,77,[79][80][81][82][83][84] • Prediction of subjective image quality from objectified measures [85] • Lesion SUV [75,86,87] • Conspicuity of pulmonary lesions [69,77,86] • Detection rate in pulmonary lesions [88] • Lesion detectability in pelvic PSMA PET/MRI at low activity [89] • Detection rate of lymph nodes in fluorocholine PET [90] • Normal databases for brain PET in neurodegenerative disease [91,92] • Acquisition time reduction [81,84,89,93] Level 2:…”
Section: Level Of Evidencementioning
confidence: 99%
“…However, this particular study did not perform reconstructions on the normal database which was provided by the software. This is in contrast to our own study which exclusively compared populations with the same PSF status, given that our normal database was reconstructed with or without PSF depending on the nature of the population investigated (5). It has been previously suggested that PET images should be smoothed to the same low spatial resolution to assess comparability between images (10).…”
Section: Discussionmentioning
confidence: 91%
“…We selected three groups of subjects that had undergone brain 18 F-FDG PET on a digital camera (Vereos, Philips ® ) with a similar acquisition protocol and reported reconstruction protocol derived from the guidelines ( 5 , 6 ). Briefly, brain 18 F-FDG PET scans were recorded over a 15 min one bed acquisition, 45–50 min after injection of 2 MBq/kg of 18 F-FDG.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation